Midwives, society, and childbirth : debates and controversies in the modern period - Marland, Hilary; Rafferty, Anne Marie (Studies in the social history of medicine., 1997)
Questioning for the first time many conventional historical assumptions, this book is fundamental to a better understanding of the effect on midwives of the unprecedented progress of science, particularly obstetric science in 20th century.